STUDI TINGKAT KEPATUHAN USAHA PENCELUPAN DI BANJAR MEKAR BHUANA KELURAHAN PAD ANGSAMBIAN, KECAMATAN DENPASAR BARAT - WINAYA, N.ANOM PURWA; MAHENDRA, M.S.; Budiarsa, I.W. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
The dyeing business potentially leads to pollution. This study aims at exploring to what extent the dyeing business adhered to 1) the permits required; 2) the system of how the waste produced should be processed; 3) awareness of dyeing companies owners on the environment. The research was conducted by observing and interviewing the owner. Two criteria were referred to in this study; criteria 1 was scored S (good) and criteria 2 was scored 1 (bad). Each component was scored depending on environmental priorities determined. The waste was tested to determine the criteria of pollution and envirovmental damage. The parameters of the waste water tested were BODS' COD, TSS, Sulfide, Phenol, Mineral Oil and Chromium (Cr). The research findings showed that ( 1) the owner did not have the standardization of permit; ( 2) the wrongly applied method turned out to disturb the expected process and was not in accordance with the criteria how the dyeing waste should be processed which was responsible for the fact that there were four chemical parameters which exceed the Standard Waste Water Of Textile Industry such as BOD 5, COD, TSS and Sulfide; ( 3) the dyeing business did not pay any attention to environment; nothing was done to contribute to environmental preser vation. Conclusion of this research is the dyeing business is not required with the three variable was be depending.
Keywords: permit, the sewage treatment plant. Attention paid to environment dyeing